ROS-responsive captopril-cinnamyl aldehyde prodrugs and compositions and methods thereof - WANG WEIPING; ZHANG YAMING (2024)
Disclosed herein are ROS-responsive prodrugs and methods of making the same. The prodrugs may contain two captopril moieties and a cinnamyl aldehyde moiety linked by a thioacetal linking moiety; when the thioacetal linking portion is cleaved by ROS, the prodrug can release two captopril or captopril derivatives and one cinnamyl aldehyde or cinnamyl aldehyde derivative. Disclosed herein are unit dosage forms of pharmaceutical formulations suitable for delivery of a prodrug to a subject in need thereof. Pharmaceutical formulations may comprise one or more additional anti-inflammatory active agents in free form. The pharmaceutical formulation may be administered by oral administration, parenteral administration, inhalation, mucosal administration, or a combination thereof. Also disclosed herein are methods for preventing or treating an inflammatory disease or disorder, or treating or ameliorating one or more symptoms associated with an inflammatory disease or disorder, in a subject. The inflammatory disease or d